Variations in the Location of Basilar Artery on Ventral Surface of Pons (Bangladesh Journal of Anatomy, 2014)
Context: Basilar artery is formed by the union of right & left vertebral arteries at the lower border of pons / mid medullary level which courses upward along Basilar groove on the anterior surface of pons & supplies the anatomical structures within the posterior cranial fossa of brain. The Circle of Willis is the principal arterial anastomotic trunk of brain formed by anastomosis between the branches of internal carotid arteries and terminal branch of basilar artery. It is responsible for collateral circulation of brain, specially of old people - who have reduced blood supply to brain due to senile arteriosclerosis. Cerebrovascular diseases due to basilar artery is more common in men than women. Anatomy of basilar artery and its branches are very complex and variable. So, detailed morphogical knowledge is essential for proper diagnosis and treatment of neurological disorder. To identify whether there is any variations in the location of basilar artery in relation to basilar groove on the ventral surface of pons . Materials and Methods: A cross-sectional descriptive type of study was carried out in the Department of Anatomy, Dhaka Medical College, Dhaka, from January 2010 to December 2010. Seventy(70) postmortem basilar arteries were collected from unclaimed dead bodies that were under examination in the morgue of Department of Forensic medicine, Dhaka Medical College Dhaka. The study was approved by the Ethical Review Committee (ERC) of Dhaka Medical College. The position of basilar artery in all the samples were either in the midline, right to midline or left to midline. Formalin fixed brain was washed with plain tap water to remove excess formalin and was kept on metallic tray. Location of basilar artery was examined carefully by hand magnifying glass and noted. Results: In the present study, location of basilar artery was found at midline in 70% brain, right to midline in 17%, left to midline in 13%. Conclusion: Further studies in large scale for preparing a database of anatomy of basilar artery are recommended. DOI: http://dx.doi.org/10.3329/bja.v11i2.20673 Bangladesh Journal of Anatomy, July 2013, Vol. 11 No. 2 pp 68-70